Thailand : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Thailand. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that a cyclical recovery is under way in Thailand but has yet to become broad based. GDP growth is estimated at 3.9 percent in 2017, boosted by strong tourism services and manufacturing exports. Domestic demand remained sluggish amid structural challenges, and export gains failed to trickle down to household incomes and investments in other sectors. Headline inflation averaged 0.7 percent, below the target band for the third year in a row, reflecting low food prices and weak core inflation. The current account surplus remained large, at about 10.6 percent of GDP. Financial system stability continued to strengthen. The growth momentum is expected to continue in 2018 and 2019, supported by sustained export dynamism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet